1965
DOI: 10.1111/j.1749-6632.1965.tb47469.x
|View full text |Cite
|
Sign up to set email alerts
|

HYPERLACTATEMIA DUE TO HYPERVENTILATION: USE OF CO2 INHALATION

Abstract: Two cases will be presented in which hyperlactatemia occurred without acidosis and the degree of lactatemia decreased significantly when CO, was administered as therapy.H~c k a b e e , ' .~ Eichenholz and collaborators,' and others' have shown that lactatemia occurs with hyperventilation, both in man and in dogs. Huckabee states that this is a form of lactatemia in which "excess lactate" does not occur, i.e., the lactate/pyruvate ratio would remain normal. I t is inferred that the condition in man is usually b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…When hypocapnea was sustained, loss of bicarbonate continued and metabolic acidosis resulted due to accumulation of lactic and pyruvic acids. Such a sequence of events has not been well documented in human beings (whereby respiratory alkalosis progressed to lactic acidosis), though marked lactic acidemia has been seen in two patients with prolonged hyperventilation caused by brainstem lesions in Wernicke's encephalopathy (Dossetor et al 1965). Montpetit et al (1971) have suggested that this is the basic mechanism for occasional elevations of lactate and pyruvate in SNE, and 1 am inclined to agree.…”
Section: Etiologic Considerationsmentioning
confidence: 99%
“…When hypocapnea was sustained, loss of bicarbonate continued and metabolic acidosis resulted due to accumulation of lactic and pyruvic acids. Such a sequence of events has not been well documented in human beings (whereby respiratory alkalosis progressed to lactic acidosis), though marked lactic acidemia has been seen in two patients with prolonged hyperventilation caused by brainstem lesions in Wernicke's encephalopathy (Dossetor et al 1965). Montpetit et al (1971) have suggested that this is the basic mechanism for occasional elevations of lactate and pyruvate in SNE, and 1 am inclined to agree.…”
Section: Etiologic Considerationsmentioning
confidence: 99%